Seasonal Price Volatility and Short-Cycle Financial Stress in Perishable Retail Markets: Evidence from 90-Day Vegetable Purchase Prices - Ghimire, Ramesh Prasad (Kshitiz Management Review, 2026)
This paper examines the extent of price changes in perishable markets of vegetables, and the resultant financial burden created for retailers. Previous studies on the problems of agriculture and supply chain management have mainly issues such as volatility, seasonality, forecasting difficulties and spoilage risk; however, little attention has been given to the negative effects of short-term procurement instability on working capital, working capital margins, and liquidity. To fill this gap, this study evaluates 90-day purchase-price data for 10 vegetables, namely cauliflower, broccoli, cucumber, green beans, cowpea, capsicum, tomato, carrot, radish, and green chili. By employing descriptive statistics, coefficients of variation, daily absolute and percentage price changes, and 30-day block comparisons, the analysis reveals significant differences in procurement risk among these commodities. Results indicate that green chili, broccoli, and cauliflower experience the highest volatility, while capsicum, cowpea, and tomato exhibit relatively more stability. Patterns observed on a daily and block-wise basis further suggest that procurement conditions change unevenly over time, with some commodities experiencing sustained upward price pressure, while others fluctuate or decrease. Such fluctuations have a direct impact on the financial health of the perishable goods retailers, which have thin margins, fluctuating resale prices and minimal storage options. The study concludes that commodity-specific purchasing strategies, liquidity planning, and enabling market policies play a key role in reducing commodity-specific short-term financial risks.